The U.S. South and Europe: Transatlantic Relations in the Nineteenth and Twentieth Centuries : edited by Cornelis A. van Minnen and Manfred Berg - Minnen, Cornelis A. van; Berg, Manfred (The University Press of Kentucky, 2013)
Front Cover; Title Page; Copyright Page; Contents ; The U.S. South and Europe: An Introduction; 1. Southerners Abroad: Europe and the Cultural Encounter, 1830-1895; 2. Alexis de Tocqueville and Three German Travel Accounts on the Antebellum South and New Orleans; 3. The Germal Forty-Eighters' Critique of the U.S. South, 1850-1861; 4. ""In the Days of Her Power and Glory"": Visions of Venice in Antebellum Charleston; 5. Elizabethan Dreams, Victorial Nightmares: Antebellum South Carolina's Future through an English Looking Glass; 6. Slavery or Independence: The Confederate Dilemma in Europe
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Geschichte 1800-2000; Europa; USA